Evaluation of the malnutrition risk status of elderly people: A cross-sectional study in three family health centers - Selin Cakmak; Emel Peker; Binnur Tagtekin Sezer; Merve Basaran; Onder Sezer (Medicine Science)
This study aimed to evaluate the malnutrition status of elderly patients by applying a mini nutritional assessment in patients aged 65 years and older. Patients aged 65 years and older who applied to family health centers numbered 22.01.009-026-047 in Edirne province were included in these study. Verbal consent was obtained, and patients were asked to answer 27 questions face to face, including the Mini Nutritional Assessment. The investigators performed the anthropometric measurements required for the assessment. The Number Cruncher Statistical System was used for statistical analysis; p [Med-Science 2024; 13(4.000): 822-8]